Properties of Analytic and Harmonic Functions / Rashida binti Omar - Omar, Rashidah (2012)
The starlikeness of integral transform V_f(z) = R 1 0 _(t) f(tz) t dt was _rst studied by Fournier and Ruscheweyh in 1994. This investigation is extended to starlikeness and convexity of order _ where _ 2 (0; 1 2 ]. Making use the class introduced by Rosihan et al. (2012b), we determine the starlikeness and convexity of order _ for the integral transforms V_f using the concept of duality and Herglotz formula. In addition, a su_cient condition for V_f to be starlike and convex functions order _ and some applications of certain operators are also looked at. Furthermore, these properties are obtained for the integral transform V_f(z) = z R 1 0 _(t) 1